Contribution of arbuscular mycorrhizal fungi to the bioavailability of micronutrients (iron and zinc) in millet accessions - Founoune-Mboup, Hassna; Diallo, Bassirou; Adigoun, Rabiath Féichokpè Raïssa; Kane, Aboubacry; Fall, Abdoulaye Fofana (Frontiers in Plant Science, 2024)
Micronutrient deficiencies, particularly iron (Fe) and zinc (Zn) deficiencies, are among the most common public health problems in developing countries. In Senegal, children under 5 years old and breastfeeding women are the most affected by zinc and iron deficiencies, respectively.Among the strategies used to alleviate micronutrient deficiencies are agronomic approaches, including soil fertilization, microbial biotechnology, and bioinoculant treatment. Zn and Fe deficiencies are often linked to the poor nutritional status of agricultural soils, leading to low quantities and/or poor availability of these nutrients in staple food crops such as pearl millet (Pennisetum glaucum L.). This study aimed to test and evaluate the contribution of two one arbuscular mycorrhizal fungal (AMF) strains (Glomus mosseae and Rhizophagus irregularis) to the bioavailability of micronutrients (zinc and iron) in the biomass of pearl millet. Eight Four pearl millet accessions from the National Laboratory for Research on Plant Production (LNRPV) collection were inoculated with two one (12) strains of AMF (Glomus mosseae and Rhizophagus irregularis) from the Common Microbiology Laboratory (LCM) collection, with four (4) replications. The data from the experiment were analyzed using Gaussian regression tests to determine the correlations between the AMF concentration and the bioavailability of micronutrients (zinc and iron) to plant biomass. The results showed that the combination of Glomus mosseae and organic residual products improved the growth parameters and micronutrient absorption of the pearl millet accessions. After analysis, the iron, zinc, phosphorus, and potassium contents of the foliar biomass of pearl millet plants were significantly greater in the mycorrhizal plants than in the nonmycorrhizal plants (control).Inoculation with AMF promoted the absorption of micronutrients (notably iron and zinc) not only in the roots but also in the aerial parts of the plants. The use of AMF and organic residual products in the cultivation of millet plants could be a good alternative for improving the development of these plants and increasing the iron and zinc contents of the varieties.